Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.5194/acpd-9-21941-2009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Atmospheric electric field anomalies associated with solar flare/coronal mass ejection events and solar energetic charged particle "Ground Level Events"

Abstract: Abstract. We discuss the fair weather atmospheric electric field signatures of three major solar energetic charged particle events which occurred in on 15 April 2001, 18 April and 4 November, and their causative solar flares/coronal mass ejections (SF/CMEs). Only the 15 April 2001 shows clear evidence for Ez variation associated to SF/CME events and the other two events may support this hypothesis as well although for them the meteorological data were not available. All three events seem to be associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 42 publications
1
13
0
1
Order By: Relevance
“…A very large (~5000 km) ionospheric disturbance of 50 mV m À1 would result in a surface electric field change of this scale (similar magnitude to electric field measured by Kasatkina et al 2009) which could induce currents of similar magnitudes to those observed in the Mitzpe Ramon J z measurements. It is likely that such large ionospheric disturbances can arise in the hours following a CME, however, effects are generally expected to be confined to high latitude regions.…”
supporting
confidence: 59%
See 2 more Smart Citations
“…A very large (~5000 km) ionospheric disturbance of 50 mV m À1 would result in a surface electric field change of this scale (similar magnitude to electric field measured by Kasatkina et al 2009) which could induce currents of similar magnitudes to those observed in the Mitzpe Ramon J z measurements. It is likely that such large ionospheric disturbances can arise in the hours following a CME, however, effects are generally expected to be confined to high latitude regions.…”
supporting
confidence: 59%
“…The fluctuations are thought to be associated with variations in the ionization rate above the UK (measured simultaneously from a balloon, but not detected by surface neutron monitors), which perturb the electric field in the lower troposphere sufficiently to induce displacement currents at the surface. Furthermore, electric field changes of 1000 V m À1 during a 10 min period were reported by Kasatkina et al (2009) at high latitudes (63.3 N) during three ground level events in 2001. The variations spread over a large area and reached down to mid-latitudes (50 V m À1 changes in E z at 47.2 N).…”
Section: Energetic Particle and Displacement Current Effectsmentioning
confidence: 92%
See 1 more Smart Citation
“…Particularly, the departure of the atmospheric electric field at middle latitudes due to substorm disturbances was examined by Kleimenova et al [2011] and the similar study had been carried out for large geo-effective storms [Sheftel et al, 1992[Sheftel et al, , 1994. In recent studies, Kasatkina et al [2009] analyzed the solar flare/ground level event's influence on the atmospheric electric field measured from the middle-to high-latitude stations and reported that the changes on the PG are subjected to many factors such as the relative Sun-Earth position, conditions in interplanetary space, and state of the ionosphere and of the atmosphere at middle and high latitudes. Moreover, the magnitude of geomagnetic substorms influencing the atmospheric electrical parameters may vary at different time periods when analyzing multiple stations becomes quite cumbersome.…”
Section: Introductionmentioning
confidence: 99%
“…This process generates and releases trapped particles and electromagnetic radiation in the form of solar X-rays and γ-ray bursts [10][11][12][13][14] . This intense radiation is responsible for ionizing the constituent particles of the ionosphere.…”
Section: Introductionmentioning
confidence: 99%